Pendekatan Consumer Centric pada Usaha Mikro Makanan Ringan dalam Perspektif Hukum Perlindungan Konsumen - Rafan Darodjat; Nun Harrieti (Yayasan Literasi Sains Indonesia, 2025)
Consumers are key determinants of business success, as the success of a food product is closely linked to its sales volume. This community engagement program was carried out through mentoring activities that emphasized the implementation of a customer-centric approach in small snack enterprises. In this approach, consumers are placed at the core of product planning, development, and marketing processes. Business actors who apply this principle are more capable of formulating strategies that correspond to customer needs, which in turn strengthens customer loyalty and increases sales performance. The training component also provided practical guidance on licensing procedures for food enterprises, grounded in the protection of consumer rights as regulated under Law No. 8 of 1999 on Consumer Protection. The program was implemented through direct mentoring and training for micro-enterprise actors. The results indicate that the customer-centric approach enhances entrepreneurs’ understanding of the importance of consumer research through segmentation analysis and product adaptation. Micro-enterprises in the food sector that adopted this approach demonstrated greater ability to design relevant business strategies aligned with customer expectations. The activity, which engaged 30 packaged-snack micro-entrepreneurs. The number of participants holding a NIB increased from 16 to 26, and several subsequently advanced to register for the SPP-IRT.